The Importance of Implementing Character Values in Learning in Elementary Schools - Istianah, Farida (International Conference on Elementary Education, 2022)
The world of education is currently facing quite a complicated problem. At a time when the government is trying to keep education going during the COVID-19 pandemic by conducting an online system. It turns out that online is not used positively by all students. Some are still hiding behind the internet by surfing in cyberspace, so there are several cases related to this. Among them is the case of online games that make students lazy to study and be active socially. This causes the erosion of the character values ​​of students as a result of the rush of foreign culture and technology that massively enters students' lives. There are so many problems that character values ​​are needed in learning. By applying character values ​​as early as possible, students are expected to become more resilient in dealing with life both at school and in society. This study identifies the implementation of character education values, using the analytical technique of Miles and Hubermen. With the stages of data reduction, data presentation, conclusions and data verification. The results showed that the process of implementing character values ​​at SDN Kedensari I can be seen from the emphasis on 3 character values ​​which include: religious, discipline and responsibility. The role of the teacher is also a very important part. Teachers are expected to be able to create learning that has character values ​​in various backgrounds and cultures so that the character values ​​of students are maintained properly.